Respuesta :
The answer is C. f(n)=f(n-1)•3
Look at the photo I attached it shows how.
Hopefully this helps. This is how I was taught.
Look at the photo I attached it shows how.
Hopefully this helps. This is how I was taught.
![Ver imagen ashway](https://us-static.z-dn.net/files/ddd/c2edcce65c9cdd76d6f533d76386cf16.png)
A recursive formula to represent the sequence: 3, 6, 9, is f(n) = f(n − 1).
The answer is option C.
What is recursion?
Recursion is the process of writing a problem or the solution to a problem in terms of a simpler form.
verifying:-
f(n) = f(n − 1) ⋅ 3
let n=1
f(n− 1) ⋅ 3
f(1 − 1) ⋅ 3=0
let n=2
f(n− 1) ⋅ 3
f(2 − 1) ⋅ 3=3
let n=3
f(n− 1) ⋅ 3
f(3 − 1) ⋅ 3=6
Learn more about recursion here:-https://brainly.com/question/1275192
#SPJ2